An integrated multi-criteria approach to formulate and assess healthcare referral system strategies in developing countries - Bouraima, Mouhamed Bayane; Jovčić, Stefan; Švadlenka, Libor; Simic, Vladimir; Badi, Ibrahim; Maraka, Naibei Dan (My University, 2024)
This study aims to identify challenges in implementing a quality healthcare referral system in developing countries and explore the strategies to overcome these challenges. Data for this study were collected through consultations with experts in the field. We introduce a novel hybrid method called Criteria Importance Assessment (CIMAS) and Alternative Ranking Order Method Accounting for Two-Step Normalization (AROMAN). CIMAS determines the relative importance of criteria, and AROMAN is employed to rank the strategies. The primary challenges identified include inadequate infrastructure facilities and deficient health information systems. The most appropriate strategy involves focusing on improving infrastructure facilities. We also carry out comprehensive sensitivity and comparative analyses to validate the applicability of the proposed model. This study identifies and elucidates the challenges of establishing a high-quality healthcare referral system in developing countries and substantially contributes to the existing body of knowledge by effectively delineating and prioritizing the strategies to tackle these challenges.
Integrovaný multikriteriální přístup k formulaci a hodnocení strategií systému doporučení zdravotní péče v rozvojových zemích
Keywords: Multi-criteria approach; Healthcare referral system; Criteria importance assessment; Two-step normalization; Developing countries; Integrovaný multikriteriální přístup; hodnocení strategií systému; zdravotní péče; rozvojové země